Upaya Meningkatkan Motivasi Belajar Dasar Dasar Jurnalistik Melalui Pelatihan Menulis Berita Terhadap Mahasiswa Kpi Angkatan 2020 & 2021 - wulandari, Uun (Journal of Media and Communication Studies, 2024)
Learning motivation is an activity that can determine effectiveness in learning. Fundamentals of Journalism is a journalist or journalist who collects news, looks for facts, and reports events. Conceptually, journalism can include 3 views, first, the process is how to find, manage, write, and publish information to the public using mass media. Second, that is, in the skill or skillful way a writer writes a story by collecting parts on writing such as coverage. And third, science is how to create and disseminate information with opinions, ideas or thoughts. Writing news is an attempt to convey information and news, be it tragedy or other information in written form. The experimental research method is included in the quantitative research method. This research uses a true experimental approach. The purpose of this research is to determine the percentage of persistence in writing news, the tenacity of interest in writing news, the tenacity to face difficulties in writing news, the desire to excel in learning to write news, independence in writing. writing news before and after training. Based on this research, it was concluded that there was a difference in the total score before and after the news writing training in an effort to increase motivation to learn the basics of journalism for KPI students for 2020/2021.